Biochemical Effects of Long-Term Exercise on Oxidative Stress and Antioxidant Markers in Adolescent Female Athletes - Ömer Faruk Bilici; Dilara Erkan; Dan Iulian Alexe; Dragoș Ioan Tohănean; Canan Demir; Cristina Ioana Alexe; Virgil Ene Voiculescu; Muhammed Fatih Bilici; Héctor Fuentes-Barria; Ulas Can Yildirim (Children)
Background: Adolescence is a critical period where exercise-induced oxidative stress is modulated by both training adaptations and hormonal changes, particularly the antioxidant effects of estrogen in females. However, data on how adolescent female athletes respond to long-term exercise remain limited. The aim of this study was to examine oxidative stress levels and some antioxidant defense parameters in adolescent female athletes who train regularly. Methods: The study included 20 adolescent female basketball players (16.65 ± 0.67 years; 165.50 ± 0.06 cm; 59.75 ± 5.50 kg) with at least three years of training experience and 20 non-athlete adolescent female participants (16.80 ± 0.69 years; 159.95 ± 0.04 cm; 60.15 ± 4.23 kg). Malondialdehyde (MDA), glutathione (GSH), and catalase (CAT) levels were analyzed by a spectrophotometric method using a UV/VIS spectrophotometer in blood samples taken from all participants, and the data were compared between the groups. Results: The results showed that MDA levels were significantly lower in the athlete group (p < 0.01; d = 4.78). In addition, CAT activity was significantly higher in athletes compared to non-athletes (p < 0.01; d = 7.81). However, no significant difference was observed in GSH levels between the groups (p > 0.05; d = 0.15). A strong negative correlation was found between MDA and CAT (r = −0.900). Conclusions: These findings suggest that prolonged exercise reduces oxidative stress and enhances catalase-mediated antioxidant defense in adolescent women. Increased CAT activity and decreased MDA levels support this effect, while stable GSH levels point to the role of compensatory mechanisms.